Privatization under the Islamic Economic System - Hussain , Kamil (Islamic Sciences Journal, 2023)
After the capitalist and socialist economic systems dominated the economic life of human society for a long period of time, people lived in them between the economic freedom of the individual without taking into account the interests of the majority, represented by the privatization of the economic system as a whole in light of the capitalist vision of the economy, and the socialist economic system that included state control over all joints Economic life without permitting the release of the economic energies of the individual, and without taking into account the innate need for love of ownership. Since the Islamic economy is based on the consideration of the individual aspect of freedom of work and ownership, taking into account the interest of society and not harming it, I thought writing about privatization under the Islamic economic system, and a statement taking into account the interest of the individual without harming the group’s interest, and putting the group’s interest before the individual’s interest, while not harming the individual’s interests. The research was divided into three sections, The first topic with ownership in terms of concept, types and characteristics, The second topic it deals with privatization, its concept, objectives, forms and effects. The third topic is devoted to talking about converting public ownership to private ownership, the extent of its permissibility, and the special controls associated with this conversion. Then I concluded the research with the most important results and some recommendations.